A associação de oxigenoterapia hiperbárica e insulinoterapia favorece propriedades biomecânicas e reparo ósseo em ratos diabéticos - Linhares, Camila Rodrigues Borges (2024)
Type 1 diabetes mellitus (DMT1) is a metabolic disease characterized by hyperglycemia due to changes in insulin secretion and/or action. Chronic hyperglycemia compromises bone metabolism, structure, and repair. Adjuvant therapies, such as hyperbaric oxygen therapy, have been proposed to improve bone structure and repair in unfavorable conditions, as occurs in DMT1. The objective of the present study was to evaluate the effects of hyperbaric oxygen therapy associated with insulin therapy on biomechanical properties and bone repair in rats with type I diabetes. For this, 48 rats were used, distributed into six equal groups. The analyses used were macroscopic analysis, microcomputed tomography (MicroCT), Fourier transforms infrared spectroscopy (FTIR), three-point bending test, and histomorphometry under light microscopy. Furthermore, the bone repair model was used to develop a new histomorphometry analysis method with an automatic approach, comparing it to manual and semi-automated methods. The results showed that type I diabetes mellitus alters the bone microstructure, anisotropy and fractal dimension, in addition reduce cortical thickness and compromise the bone matrix composition and hardness. However, combined treatments of hyperbaric oxygen therapy and insulin therapy have been shown to reduce these adverse effects, suggesting significant therapeutic potential for managing bone complications in diabetic patients. The proposed automated method of histomorphometry analysis, as well as the manual and semi-automated methods, were effective in measuring bone formation, without significant statistical differences between them. However, the automatic approach significantly reduced the time required for analysis compared to manual and semi-automated methods. It was concluded that the association of therapies with hyperbaric oxygenation and insulin reduces the negative effects of hyperglycemia in diabetic rats, improving bone properties and regeneration. And, the automated method offers a fast and accurate assessment, with the potential to reduce bias and standardize histomorphometry analysis, suggesting that this technique can be used reliably to quantify bone matrix.